Chinese Paintings in Chinese Publications, 1956-1968 An Annotated Bibliography and Index to the Paintings - Johnston Laing, Ellen (Michigan Monographs In Chinese Studies, 2020)
This bibliography includes publications issued between 1956 and August 1968 that reproduce Chinese paintings now in Chinese public or private collections. The great majority of these publications were produced in Mainland China, Taiwan, Hong Kong, or Japan. Each publication included in the bibliography has been provided with a detailed physical description of the publication itself: the amounts of text , the number of plates in color and in monochrome, and a general evaluation of the quality of the reproductions. The title by which each work is referred to in the index is included at the end of each entry.